A Combined Atomistic-Continuum Study on the Unfaulting of Single and Multi-layer Interstitial Dislocation Loops in Irradiated FCC and HCP Metals. (May 2022) - Chen, Cheng; Song, Jun
Highlights: Comprehensive combined atomistic-continuum modeling was performed to study unfaulting of interstitial Frank loops in FCC and HCP metals. For FCC metals, mechanisms and detailed dislocation reaction intermediates for two unfaulting pathways, i.e., double Shockley (D-Shockley) partial unfaulting and Frank loop periphery unfaulting, were fully clarified. For HCP metals, a comprehensive mapping of the transition pathways (and associated conditions) between different double interstitial loop morphologies were obtained, with comparison with experimental observations. A new predictive model able to accurately predict the threshold conditions for unfaulting of interstitial loops in irradiated FCC and HCP metals was developed. The new modeling techniques and predictive tools are generic and can be readily extended to investigation of other complex dislocation or defect ensembles. Abstract: Unfaulting of single and multi-layer interstitial loops in face centered cubic (FCC) and hexagonal close-packed (HCP) metals, with Ni, Al, Mg and Zr as model systems, have been comprehensively studied employing molecular dynamics simulations and continuum modeling. A versatile approach properly accounting for atom insertion/removal and displacement field was developed, able to correctly construct single and multi-layer interstitial loop structures of arbitrary geometries. The unfaulting mechanisms and corresponding dislocation reaction intermediates in different unfaulting scenarios were clarified. Critical conditions necessary for unfaulting have been identified, and an analytical model has been developed to accurately predict these conditions. Particularly for unfaulting in FCC materials, the role of Double Shockley ( D -Shockley) partial in unfaulting has been explicitly elucidated, and the mechanisms of unfaulting initiating from periphery of the Frank loop and induced by a moving straight edge dislocation have been clarified. For unfaulting in HCP, despite certain similarity to its FCC counterpart, clear difference in unfaulting behaviors due to the HCP stacking sequence has been demonstrated. A comprehensive mapping of unfaulting routes for double-layer interstitial loops in HCP has been established to reveal the relationships between the various loop morphologies observed in experiments. The present work provides important mechanistic insights to address key knowledge deficits regarding interstitial Frank loop unfaulting, essential for better understanding of deformation and irradiation-induced failure in structural metals. The new modeling techniques and predictive tools offered are expected to be of great merits to not only the study of unfaulting of dislocation loops, but also future investigation of other complex dislocation or defect ensembles. Graphical abstract: Image, graphical abstract